Atrial Natriuretic Peptide Antibody-Functionalised, PEGylated Multiwalled Carbon Nanotubes for Targeted Ischemic Stroke Intervention - Patrick P. Komane; Pradeep Kumar; Yahya E. Choonara (MDPI AG, 2021)
Stroke is one of the major causes of disability and the second major cause of death around the globe. There is a dire need for an ultrasensitive detection tool and an effective and efficient therapeutic system for both detection and treatment of stroke at its infancy stage. Carbon nanotubes are promising nanomaterials for tackling these challenges. The loading of dexamethasone and decoration of PEGylated multiwalled carbon nanotube with atrial natriuretic peptide (ANP) antibody and fluorescein isothiocyanate for targeting ischemic site in the rat stroke model is presented here. Functionalisation of carbon nanotubes with dexamethasone (DEX), polyethylene glycol (PEG), fluorescein isothiocyanate (FITC), and ANP antibody caused a 63-fold increase in the D band intensity as illustrated by Raman. The characteristic band intensity increase was observed at 1636 nm following functionalisation of carbon nanotubes with polyethylene glycol and dexamethasone as confirmed by Fourier Transform Infrared. These findings have demonstrated the coupling capability of atrial natriuretic peptide antibody to DEX-PEG-CNTs. The baseline plasma atrial natriuretic peptide levels were ranging from 118 to 135.70 pg/mL prior to surgery and from 522.09 to 552.37 following common carotid artery occlusion. A decrease in atrial natriuretic peptide levels to 307.77 was observed when the rats were treated with FITC-DEX-PEG-ANP-CNTs, PEG-CNTs and DEX with a significant drop in the FITC-DEX-PEG-ANP-CNTs treated group. Fluorescence was detected in FITC-DEX-PEG-CNTs and FITC-DEX-PEG-ANP-CNTs treated ischemic stroke rats. The highest fluorescence intensity was reported in plasma (2179) followed by the kidney (1563) and liver (1507). These findings suggest a beneficial role that is played by the FITC-DEX-PEG-ANP-CNTs in the reduction of inflammation in the ischemic stroke induced rats that could induce a successful treatment of ischemic stroke.